Implementasi Program Kampus Mengajar (Studi Pada Civitas Akademika Universitas Pawyatan Daha) - Rizki Fillya Curtinawati; Nanda Erlambang; Endang Handini (FISIP UWP, 2024)
Merdeka Belajar-Kampus Berdeka (MBKM) policy, as a government effort to prepare students to face the world of work and technological advances. One of them is the Teaching Campus Program as an effort to provide opportunities for students to learn outside the classroom by becoming teacher partners in the learning process in primary and secondary education units, hereinafter referred to as assignment schools. To see how the implementation of the Teaching Campus Program, the researcher used a qualitative descriptive method. The results of the research that The implementation of the MBKM-Campus Teaching Program at Pawyatan Daha University has gone quite well. Between the Teaching Campus Program run by UPD, the Program Implementation by the Leaders and Persons in Charge of the Faculty/Prodi and the Program Target, namely UPD students themselves, have achieved compatibility so that these aspects support each other in implementing the Teaching Campus Program, even though there are a few obstacles in each aspect.